Recent work on intellectual humility: A philosopher's perspective. Issue 2 (4th March 2023) - Ballantyne, Nathan
ABSTRACT: Intellectual humility is commonly thought to be a mindset, disposition, or personality trait that guides our reactions to evidence as we seek to pursue the truth and avoid error. Over the last decade, psychologists, philosophers, and other researchers have begun to explore intellectual humility, using analytical and empirical tools to understand its nature, implications, and value. This review describes central questions explored by researchers and highlights opportunities for multidisciplinary investigation.